Dynamic Monte Carlo Simulation of the l, l‐Lactide Ring‐Opening Polymerization. Issue 1 (31st August 2016) - Meimaroglou, Dimitrios; Pladis, Prokopios; Kiparissides, Costas
Abstract : In the present study, a comprehensive theoretical kinetic investigation of the homopolymerization ofl, l ‐lactide in the presence of stannous octoate Sn(Oct)2 as initiator for the synthesis of high‐molecular weight polylactide is carried out using the stochastic Monte Carlo numerical method. Abstract : In the present study, a comprehensive theoretical kinetic investigation of the homopolymerization ofl, l ‐lactide in the presence of stannous octoate Sn(Oct)2 as initiator for the synthesis of high‐molecular weight polylactide is carried out using the stochastic Monte Carlo (MC) numerical method. A comprehensive mathematical model is developed based on a detailed kinetic mechanism to predict the dynamic evolution of monomer conversion and molecular weight distribution. The validity of the implemented kinetic model and the accuracy of the produced simulation results are assessed via a direct comparison with theoretical predictions of the average molecular properties by the method of moments as well as with available experimental data. The effects of monomer to initiator molar ratio and polymerization temperature on the polymerization rate and average molecular weight properties of polylactide are studied.